The effect of asymmetry of the coil block on self-assembly in ABC coil-rod-coil triblock copolymers - Han, X.-G.; Meng, H.-H.; Ma, Y.-H.; Ouyang, S.-L. (Condensed Matter Physics, 2017)
Using the self-consistent field approach, the effect of asymmetry of the coil block on the microphase separation is focused in ABC coil-rod-coil triblock copolymers. For different fractions of the rod block fB, some stable structures are observed, i.e., lamellae, cylinders, gyroid, and core-shell hexagonal lattice, and the phase diagrams are constructed. The calculated results show that the effect of the coil block fraction fA is dependent on fB. When fB = 0.2, the effect of asymmetry of the coil block is similar to that of the ABC flexible triblock copolymers; When fB = 0.4, the self-assembly of ABC coil-rod-coil triblock copolymers behaves like rod-coil diblock copolymers under some condition. When fB continues to increase, the effect of asymmetry of the coil block reduces. For fB = 0.4, under the symmetrical and rather asymmetrical conditions, an increase in the interaction parameter between different components leads to different transitions between cylinders and lamellae. The results indicate some remarkable effect of the chain architecture on self-assembly, and can provide the guidance for the design and synthesis of copolymer materials.